The Judicialization of Politics on the Testing of the Constitutionality of the Age Limits of Presidential and Vice Presidential Candidates by the Constitutional Court - Khan, Azizah Ratu Buana; Agustin, Ruli (Dinasti Research, 2024)
The phenomenon of the Judicialization of Politics within the Constitutional Court can be seen in the differences in several decisions of the Constitutional Court in reviewing the constitutionality of Law Number 7 of 2017 concerning General Elections regarding the minimum age limits for presidential and vice presidential candidates. Decisions Number 29/PUU-XXI/2023, 50/PUU-XXI/2023, 51/PUU-XXI/2023, and 90/PUU-XXI/2023 have the same outline of the petition but have different results. The research method used is juridical-normative legal research to fully view the phenomenon of judicialization of politics within it. The open legal policy decisions in the three decisions are different from one other decision so that this should be appropriate to return to the legislators as a whole and not the territory of the Constitutional Court